Who Uses Commercial Lobbying Firms - Eric Richert; Brittany Feor; Blair Long (Queen's University, Department of Economics, 2018)
This paper explains the type of interest groups that use commercial lobbyists and the types of groups that lobby directly or are excluded from access to politicians. The main results provide evidence that commercial lobbying and donations by these firms to politicians can improve policy outcomes by increasing the number of groups that the politician can trust. Special interest groups come up with policy proposals that may be good or bad for society. They also get a benefit of having their idea implemented regardless of its overall social benefit so cannot be trusted to present their policy only when it is good for society. We show that repeated interaction with a policy maker can incentivize truthful communication. Therefore, interest groups working on highly salient issues or who work on issues with mostly high social benefits, can lobby alone, while interest groups who work on less salient issues or are less reputable need to use a commercial lobbyist to be trusted by the politician. Finally, firms of the lowest quality or salience are excluded from influencing the policy maker.
Keywords: D72; D83; H11; P16; 330; Commercial Lobbying; Political Access; Strategic Communication; Repeated Contracts